Microfiber Mach-Zehnder interferometer embedded in low index polymer - Sulaiman, Azlan; Harun, Sulaiman Wadi; Lim, Kok Sing; Ahmad, Fauzan; Ahmad, Harith (Elsevier, 2012)
Microfiber Mach Zehnder Interferometer (MMZI) is demonstrated by micromanipulating an optical microfiber drawn from a single mode fiber (SMF) using a flame brushing technique. The MMZI shows good interference fringes with an extinction ratio of 13 dB and a free spectral range (FSR) of 0.52 nm at 1530 nm. The MMZI is then embedded in a polymer with the refractive index of 1.36 to increase the stability and robustnes of the device. It is found that the transmission spectrum of the packaged MMZI is changed by the polymer, which increases the FSR to 0.83 nm. The degradation in transmission loss and extinction ratio are attributed to the disturbance at the coupling area during the packaging. Compared with waveguide based mach zehnder interferometer, the proposed MMZI is favoured due to easy fabrication, compact size, and easy integration with the fiber system.